Sexual abstinence as a reproductive health-promoting behavior for women: A perspective - La-Ongdao Wannarit (Belitung Raya Foundation, Indonesia, 2022)
This article is intended to provide an appropriate context for adopting sexual abstinence from a health-promoting behavioral perspective that can be applied to women of reproductive age worldwide to improve reproductive health, maintain well-being, and prevent health problems in women. The topics related to women’s health status, sexual abstinence definitions, benefits, and application, as well as sexual autonomy and efficacy, including family collaboration, are discussed. This article will provide health care providers, especially nurses and midwives, with new ideas for integrating sexual abstinence into nursing and midwifery practice.